Investigating associations between social determinants, self-efficacy measurement of sleep apnea and CPAP adherence: the SEMSA study - Gentina, Thibaut; Gentina, Elodie; Douay, Bernard; Micoulaud-Franchi, Jean-Arthur; Pépin, Jean-Louis; Bailly, Sébastien (Frontiers in Neurology, 2023)
Study Objectives: The prospective Self-Efficacy Measure for Sleep Apnea study (SEMSAS) is investigating thresholds for health literacy, self-efficacy and precariousness at obstructive sleep apnea (OSA) diagnosis to predict CPAP adherence. This paper describes the study protocol and presents baseline data from the ongoing study. Methods: Eligible individuals had confirmed OSA and were referred to a homecare provider for continuous positive airway pressure (CPAP) therapy initiation. Data on patient characteristics and comorbidities were collected, along with baseline evaluations of self-efficacy (15-item Self-Efficacy Measure for Sleep Apnea tool [SEMSA-15]), precariousness (Deprivation in Primary Care Questionnaire [DipCareQ]), and health literacy (Health Literacy Questionnaire). CPAP adherence over 12 months of follow-up will be determined using remote monitoring of CPAP device data. The primary objective is to define an optimal SEMSA-15 score threshold to predict CPAP adherence at 3- and 12-month follow-up. Results: Enrollment of 302 participants (71% male, median age 55 years, median body mass index 31.6 kg/m2) is complete. Low self-efficacy (SEMSA-15 score ≤2.78) was found in 93/302 participants (31%), and 38 (12.6%) reported precariousness (DipCareQ score >1); precariousness did not differ significantly between individuals with a SEMSA-15 score ≤2.78 versus >2.78. Health literacy was generally good, but was significantly lower in individuals with versus without precariousness, and with low versus high self-efficacy. Conclusions: SEMSAS is the first study using multidimensional baseline assessment of self-efficacy, health literacy and precariousness, plus other characteristics, to determine future adherence to CPAP, including CPAP adherence trajectories. Collection of follow-up data is underway.